MOBILE COFFEE SME VISUAL IDENTITY REDESIGN TO INCREASE BRAND AWARENESS - Muh. Husriadi; La Ode Ramalan; Aini Ashary (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Mobile coffee SMEs in Kendari face the challenge of inconsistent visual identities, hindering brand awareness amidst intense competition in the coffee market. This study aims to explore the visual identity redesign process, implementation constraints, and its impact on consumer perceptions. A qualitative case study approach was used, with in-depth interviews, participant observation, and thematic analysis of Kendari SMEs. The results show that the redesign improved visual element consistency, overcame funding limitations through local collaboration, and optimized social media platforms, accelerating brand awareness by up to 40% via digital engagement. The findings contribute to the branding model for micro-SMEs and have practical implications for empowering local economies through inclusive technology